The influence of exercise and BMI on injuries and illnesses in overweight and obese individuals: a randomized control trial - Janney Carol A; Jakicic John M (BMC, 2010)
Abstract Background Medically treated injuries have been shown to increase with increasing body mass index (BMI). Information is lacking on the frequency and type of injuries and illnesses among overweight and obese adults who engage in regular physical activities as part of weight loss or weight gain prevention programs. Methods Sedentary adults with BMIs between 25 and 40 kg/m2 (n = 397) enrolled in one of two randomized clinical trials that emphasized exercise as part of a weight loss or weight gain prevention program. Interventions differed by duration of the exercise goal (150, 200, or 300 minutes/week or control group). Walking was prescribed as the primary mode of exercise. At six month intervals, participants were asked, "During the past six months, did you have any injury or illness that affected your ability to exercise?" Longitudinal models were used to assess the effects of exercise and BMI on the pattern of injuries/illnesses attributed to exercise over time; censored linear regression was used to identify predictors of time to first injury/illness attributed to exercise. Results During the 18-month study, 46% reported at least one injury/illness, and 32% reported at least one injury that was attributed to exercise. Lower-body musculoskeletal injuries (21%) were the most commonly reported injury followed by cold/flu/respiratory infections (18%) and back pain/injury (10%). Knee injuries comprised one-third of the lower-body musculoskeletal injuries. Only 7% of the injuries were attributed to exercise alone, and 59% of the injuries did not involve exercise. BMI (p ≤ 0.01) but not exercise (p ≥ 0.41) was significantly associated with time to first injury and injuries over time. Participants with higher BMIs were injured earlier or had increased odds of injury over time than participants with lower BMIs. Due to the linear dose-response relationship between BMI and injury/illness, any weight loss and reduction in BMI was associated with a decrease risk of injury/illness and delay in time to injury/illness. Conclusions Overweight and obese adults who were prescribed exercise as part of weight loss or weight gain prevention intervention were not at increased risk of injury compared to overweight adults randomized not to participate in prescribed exercise. Since onset of injury/illness and pattern of injuries over time in overweight and obese individuals were attributed to BMI, weight reduction may be an avenue to reduce the risk of injury/illness in sedentary and previously sedentary overweight and obese adults. Trial Registration Clinicaltrials.gov NCT00177502 and NCT00177476